Recommendations on the transport of dangerous goods : manual of tests and criteria - United Nations. Committee of Experts on the Transport of Dangerous Goods (1957- ); United Nations (Geneva : United Nations, 1995)
This book tries to explain what happened in the Haight-Ashbury section of San Francisco. For it was in the Haight that whatever happened, happened most vividly and so intensely that it drew international attention to itself.
"The recommendations in this Manual of tests and criteria supplement the Recommendations on the transport of dangerous goods and result from the decisions of the United Nations Committee of Experts on the Transport of Dangerous Goods."--Foreword.
"United Nations publication sales no. E.95. VIII.2"--Title page verso.
"ISSN 1014-5753"--Title page verso.
oif 11/08/15
Loan
Keywords: Hazardous substances -- Transportation -- Law and legislation; Hazardous substances -- Transportation -- Safety regulations; Hazardous substances -- Testing